Study on Analysis of Vitamin C and Î²-Carotene Levels From Tamarillo (Solanum betaceaum Cav.) Fruit Produced Between Shoot Grafting of Tamarillo with Lancing Plant (Solanum mauritianum) - Zaidar, Emma; Safitri, Irma; Yusak, Yuniarti (Talenta Publisher, 2021)
Research on studies analysis levels of vitamin C and Î²-carotene of the Tamarillo fruit shoot grafting between the Tamarillo plant and Lancing plant has been conducted. Analysis of vitamin C level was performed by iodometric method, and analysis of Î²- carotene levels were calculated using UV-Vis spectrophotometer. The research result showed that the level of vitamin C of Tamarillo fruit was 1.596%, the level of vitamin C of Lancing fruit was 0.401%, and the level of vitamin C of Tamarillo fruit grafting outcomes was 1.202%. While the level of Î²-carotene of Tamarillo fruit was 208.95 ppm, the level of Î²-carotene of Lancing fruit was 36.11 ppm and the level of - carotene of Tamarillo fruit grafting outcomes was 253.64 ppm. It can be concluded that the vitamin C levels of Tamarillo fruit grafting outcomes decreased slightly. While the Î²-carotene levels of Tamarillo fruit grafting outcomes increased.